Treatment of ulcerative colitis in the cottontop tamarin using antibody to tumour necrosis factor alpha. - Watkins, P E (1997)
BACKGROUND: The aetiology and pathophysiology of ulcerative colitis remains unclear; however, there is increasing recognition of the critical role of inflammatory cytokines in the pathogenesis of this disease. Among these, tumour necrosis factor alpha (TNF alpha) seems to play an important role. AIM: To study the effects of an engineered human monoclonal antibody to TNF alpha (CDP571) in the treatment of idiopathic ulcerative colitis in the cottontop tamarin. METHODS: Six cottontop tamarins with confirmed ulcerative colitis received repeated doses of CDP571. Progression of disease was assessed by measuring both body weight and rectal biopsy pathology. RESULTS: All animals showed a rapid improvement in clinical condition and rectal biopsy pathology that was maintained following completion of the therapy. CONCLUSION: These studies indicate the efficacy of selective antibody therapy to TNF alpha for the treatment of ulcerative colitis in a primate and suggest that similar therapy in human could be of value.